Atos violentos e mediação de conflitos na educação superior: da reflexão à ação - Souza, Ana Paula Correia de (2020)
This research has as general objective of elaboration of proposals that support the Centro Universitário UDF in the introduction of conflict mediation mechanisms that contribute to the improvement of the school environment of this University Center. To identify the types of conflicts that occur in this institution and the mechanisms that currently exist for the purpose of dealing with such conflicts, were analyzed exploratory qualitative study of the occurrence books and disciplinary proceedings instituted from 2016 to 2018. After analyzing the institutional documents, the data obtained were tabulated from the previous categories elaborated by Vóvio et. al. (2016) and adapted to higher education. In this study, conflict was understood as a natural consequence of life in society, which stems from the defense of different positions defended against others in the light of Álvaro Chrispino (2007), and violence, conceptualized as a relative phenomenon, because it is the result of a social construction, in which it will depend on a number of factors, such as the historical and cultural context, among others, that attribute a character of dynamism and mutability inherent to social events, considering the notes of Abramovay (2006). It is concluded that among the conflicts and violent acts registered, with 61% of the occurrences, the violent acts “to” IES prevail and that 21% of these records were related to depredations and 37% were related to thefts or thefts of the institutional patrimony, with 58% of the violent acts suffered by the institution are of patrimonial order and that the patrimonial violence corresponds to 38% of all cataloged records; physical violence corresponds to 10%; moral (or symbolic) violence corresponds to 33% and nonviolent acts correspond to 12.8%. It was also found that there is no normative instrument about the forms of institutional conflict resolution. Given the data found, a proposal is presented suggesting the introduction of the theme “conflict mediation” in the academic community; the training of members of the Disciplinary Commission for the practice of conflict mediation; the implementation of initiatives that encourage the sense of belonging to the University Center and the development of a democratic management line.